PMM.19 Sertoli Leydig Cell Tumour in Pregnancy. (9th June 2014) - Imcha, M; Egbase, E; Ismail, M; Ross, G
Abstract : Background: Sex cord stromal tumours make up less than 0.2% of tumours in the ovaries and about 1% of ovarian malignancies during pregnancy. Their unpredictability makes counselling, management, and prognosis challenging. This case of intermediate grade Sertoli-Leydig cell tumour of FIGO stage 1c during pregnancy had exploratory staging at 20 weeks gestation with adjuvant chemotherapy followed by uncomplicated pregnancy and delivery. Case: Patient aged 25 at 8 weeks gestation had abdominal pains. Initial scan showed singleton intrauterine viable pregnancy with incidental finding of large irregular multiloculated, septated, and nonvascular complex cyst on right adnexa with probable origin from right ovary. Follow up plan included repeat scans, MRI and blood test for tumour markers to investigate nature of the cyst. MRI scan at 13 weeks showed free fluid in pelvis, with recent significant growth, and suspicious features of malignancy with solid areas and abnormal vascular flow. Recommendation from Multi-Disciplinary Team was for surgery and if confirmed malignancy, for chemotherapy. Patient had mid-trimester laparotomy. Histology showed intermediate grade Sertoli- Leydig cell tumour with focal high grade areas. It was determined as FIGO stage 1c. She had adjuvant chemotherapy at 28 weeks gestation and normal delivery at 38 weeks gestation. Conclusion: This rare case demonstrates treatment and follow up procedure in absence of availability of an evidence-based approach. Patient's age, tumour stage and degree of differentiation are used to determine the treatment and need for chemotherapy. Surgical intervention is usually after 14 weeks gestation. Chemotherapy should be considered for cases of advanced stage.